2020
DOI: 10.1016/j.heliyon.2020.e04220
|View full text |Cite
|
Sign up to set email alerts
|

The C-reactive protein to albumin ratio predicts postoperative complication in patients who undergo gastrectomy for gastric cancer

Abstract: The aim of this study was to evaluate the preoperative C-reactive protein (CRP) to albumin ratio (CAR) of patients with gastric cancer and to investigate the factors correlated with perioperative complications. From March 2016 to December 2019, 128 patients who underwent curative gastrectomy for gastric cancer were enrolled in a retrospective study. The preoperative cutoff value of the CAR for predicting postoperative complications was 0.265 on receiver operating characteristic (ROC) curve analysis. Clinical c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…CAR, as a novel index, has proved to provide useful prognostic information for sepsis, abdominal surgeries, cancer, or emergency laparotomy. 10 , 11 , 12 , 13 , 30 However, the cut‐off selected for use are often inconsistent, even quite different. For example, Hu et al 31 used 0.24 as cut‐off value to predict the overall survival in patients with osteosarcoma and Shi et al used 0.27 to predict periprosthetic joint infection, both of which were 3‐fold as ours (0.09); while in a study of gastric cancer, Aoyama et al 12 found the optimal cut‐off point of CAR was 0.05 to optimally evaluate the overall survival and recurrence‐free survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR, as a novel index, has proved to provide useful prognostic information for sepsis, abdominal surgeries, cancer, or emergency laparotomy. 10 , 11 , 12 , 13 , 30 However, the cut‐off selected for use are often inconsistent, even quite different. For example, Hu et al 31 used 0.24 as cut‐off value to predict the overall survival in patients with osteosarcoma and Shi et al used 0.27 to predict periprosthetic joint infection, both of which were 3‐fold as ours (0.09); while in a study of gastric cancer, Aoyama et al 12 found the optimal cut‐off point of CAR was 0.05 to optimally evaluate the overall survival and recurrence‐free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation‐based prognostic factors have attracted increasing attention in multiple settings, largely because they combine the systemic inflammatory status and pathological burden. C‐reactive protein to albumin ratio (CAR) has demonstrated its effectiveness in predicting clinical outcomes or adverse events in a range of conditions, for example, cancers of liver, 9 lung, 10 pancreas 11 and intestines/stomach, 12 , 13 severe burn injury, 14 or musculoskeletal disorders. 15 , 16 , 17 Specified at postoperative infection, Goulart et al 18 identified CAR on postoperative day 3 as an independent predictor after colorectal cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those authors reported that a high CAR was an independent risk factor for surgical site infection (22). In addition, Lee et al evaluated the relationship between the CAR and perioperative surgical complications in 128 patients with gastric cancer (24). They demonstrated that the CAR was an independent prognostic factor of perioperative surgical complications (HR=2.832, p=0.045).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Saito et al evaluated the CAR as a prognostic factor in 453 patients with stage I-IV gastric cancer, setting the cut-off value at 0.0232 according to a receiver operating characteristic analysis (30). Toiyama et al evaluated the CAR as a prognostic factor in 384 patients with stage I-III gastric cancer (24), setting the cut-off value at 0.051 according to their own receiver operating characteristics analysis. In addition, Li et al evaluated the CAR as a prognostic factor in 258 patients with stage IV gastric cancer (26), setting the cut-off value at 0.5897.…”
Section: Discussionmentioning
confidence: 99%
“…Among the markers using albumin and CRP, unlike GPS and mGPS, which are classified as absolute values, CAR is a useful index indicating the ratio of albumin and CRP. Several previous studies have suggested that the CAR value can reflect the postoperative short-term outcomes in various kinds of diseases [ 78 , 79 ]. There are also papers analyzing the correlation between postoperative morbidity and preoperative CAR in CRC patients.…”
Section: Markers Available Through Blood Chemistry Testsmentioning
confidence: 99%